2020
DOI: 10.3389/fimmu.2020.559635
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid Signaling in Intestinal Epithelial Cells Is Essential for Early Survival From Gastrointestinal Infection

Abstract: Vitamin A deficiency (A-) increases morbidity and mortality to gastrointestinal (GI) infection. Blocking retinoid signaling (dominant negative retinoic acid receptor, dnRAR) in intestinal epithelial cells (IEC, IEC dnRAR) had no effect on vitamin A absorption, the expression of tight junction proteins or the integrity of the barrier. Immune cells in the gut were present in normal frequencies in the IEC dnRAR mice, with the exception of the T cell receptor (TCR)αβ+/CD8αα cells, which were significantly lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We are interested in how micronutrients, in particular vitamin A, regulates this process given the well-established beneficial effects of this molecule in maintaining mucosal barrier function. Indeed, recent studies have shown the crucial role of intestinal epithelial retinoid signaling in regulating the survival of mice in the context of GI infection ( 37 ). In this paper, we provide novel insights into how retinoic acid signaling influences intestinal tight junctions and microbiota in the setting of allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…We are interested in how micronutrients, in particular vitamin A, regulates this process given the well-established beneficial effects of this molecule in maintaining mucosal barrier function. Indeed, recent studies have shown the crucial role of intestinal epithelial retinoid signaling in regulating the survival of mice in the context of GI infection ( 37 ). In this paper, we provide novel insights into how retinoic acid signaling influences intestinal tight junctions and microbiota in the setting of allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is essential for developing adaptive immunity to intestinal microorganisms and is an anti-inflammation vitamin because it is critical in enhancing immune function. Hence, its deficiency can be detrimental to the animals’ intestinal health [ 118 , 119 , 120 ]. Vitamin A supplementation in piglets (14 days post-weaning) improved their intestinal morphology and activity of digestive enzymes, positively affecting the piglets’ intestinal function [ 88 ].…”
Section: Small Intestinementioning
confidence: 99%
“…Postnatal local RA synthesis and signaling is essential for maintenance of epithelial homeostasis (Wolbach and Howe, 1925), immune function (Hall et al, 2011), and stem cell populations (Strickland and Mahdavi, 1978). Role of RA in maintaining a robust intestinal epithelium barrier is especially important in regulating host microbe interactions (Gattu et al, 2019;Snyder et al, 2020). Loss of intestinal epithelial cell (IEC) intrinsic RA signaling in mice results in defective goblet cell lineage commitment and reduced epithelial cell shedding upon infection (Iyer et al, 2020;Jijon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%